Asynchronous gateway reallocation communication in heterogeneous 5G networks. (20th July 2020) - Kodavati, Baburao; Ramarakula, Madhu
Summary: Background: Smart vision of the world is the latest challenge believing that 5G networks could feed all of our internet device needs. The exchange of information (data) needs not to go through backhaul because lots of capabilities will be available close to where it is needed. Presently, the majority of communications are based on single‐mode transmission. Communications will be more responsive and interactive due to 5G technology. The implementation of 5G faces various problems. It is necessary to improve the network capacity by densification, increasing spectrum, and measuring the spectral efficiency. And it also needs to reduce the latency, and it must be energy efficient. Purpose: It is fit for inter‐access service network (ASN) (asynchronous) communications due to the incapability to maintain vertical handoff communications. The need for vertical handovers hinges on various factors that need to be analyzed concurrently with the signal strength in heterogeneous wireless environment. Methodology: Thus, it proposed to utilize a vertical handover decision algorithm centered on the priority and speed of the subscriber. Implementation confirms the claim of the proposed method to achieve better channel utilization and maintains the QoS requirements of the mobile users. Findings: Time latency calculation, evaluation of energy utilization between different nodes, and performance analysis packet loss are evaluated. Conclusion: Better efficiency is attained for data transmission among the users that is one mobile node to other with commercial event management and appropriate processing in each node. Abstract : A vertical handover decision algorithm focused on the priority and speed of the subscriber. Implementation confirms the claim of the proposed method to achieve better channel utilization and maintains QoS requirements of mobile users. The time latency calculation, evaluation of energy utilization between nodes and performance analysis packet loss are evaluated. It provides better efficiency for data transmission among the users that is one mobile node to other with commercial event management and appropriate processing in each node.